Microfinance program and food security: A Review in the Indonesian context - Endar Purnawan; Gianluca Brunori (President University Press, 2022)
This paper addresses the way microfinance programs affect food security, whic h is compiled based on a literature review of a total of 58 pieces of literature, from 1995 to 2020. Its paper sheds light on microfinance in rural areas in Indonesia, microfinance and food security, and critics related to microfinance programs based on a literature review. The result indicates that when the program’s impact on participants’ families’ food security and nutrition is measured, the results could be different. Most of the results stated a positive impact, but it might depend on many other factors. Taken together, the paper findings highlight the importance of a cycle of innovation, experimentation, and evaluation that must be carried out to build a robust financial institution to answer challenges and provide solutions to all the various conditions experienced by low-income families, involving various institutional structures, modes, and mechanisms. Other supporting factors are also important, including community involvement, the availability of safety nets, and non-financial support in many fields, such as increasing institutional capacity, business development, technology utilization, procurement, production, and, most importantly, marketing.